การเลือกนำกลับนิกเกิลจากน้ำเสียในอุตสาหกรรมเหล็กกล้าไร้สนิมโดยเยื่อแผ่นเหลวที่พยุงด้วยเส้นใยกลวง - ยุทธพงษ์ เข็มกลัด (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The extraction and selective recovery or stripping of nickel ions from wastewater in the stainless steel industry by hollow fiber supported liquid membrane was studied. The effects of the pH of feed (wastewater), types of the extractants, concentrations of the extractant and stripping solutions, flow rates of feed and stripping solutions, and volumetric ratio of feed to stripping solutions were investigated. The extractants, i.e., D2EHPA, Cyanex 301, Cyanex 272 and LIX 860-I were dissolved in kerosene as a membrane solution, which was supported by a microporous hydrophobic hollow fiber membrane extractor. Sulfuric acid was served as the stripping solution. Feed and stripping solutions flowed countercurrently. Consequently, two consecutive modules of hollow fiber were applied for a higher recovery of nickel ions. The optimum conditions of a single-module operation were same as those of 2-module operation. The results showed that LIX 860-I was the most effective to extract as well as selectively retrieve nickel ions from wastewater at a feed pH of 4. The percentage of the recovery of nickel ions increased with the concentrations of LIX860-I and sulfuric acid of (0.5-2.5 M). However, it decreased after the concentration of LIX 860-I was higher than 0.8 M. More nickel ions were recovered at the flow rates of feed and stripping solutions of 100 ml/min and reduced when the flow rates increased. In addition, in this study equal volume of feed and stripping solutions of 3500:3500 (ml:ml) is recommended to attain more nickel ions recovery. The maximum extraction and selective recovery of nickel ions by a single-module operation are 87% and 58%, and 98%, and 87% by 2-module operation. The amount of nickel ions remained in the feed solution after passing 2-module operation is 1 ppm, which is in accordance with the permissible limit of Thailand.